O Distrito Industrial de Santa Maria - RS: instalação e novas perspectivas - Lima, Bruna (2014)
The idea of creating an industrial district of Santa Maria originated in the mid -1960s as a possible solution to the problem of industrialization and labour of the city. Its creation was also in line with the pursuit of accelerated economic growth, experienced by the Civil-Military Dictatorship by which spent Country, during the late 1960s and early 1970s and the policy of dissemination of industrial areas in Rio Grande do Sul. In this context, we seek to understand how the installation of the Industrial District of Santa Maria occurred and what are the main problems for him now, considering that the city still has not reached the expected level of industrialization. The alternatives that aimed to reverse this situation were also the target of study. For this, besides references were used for the preparation of this work, documents like the Bill and Feasibility Study of the Industrial District of Santa Maria, the Master Plan of the city, Reports of committees aimed to make allowances for the execution of Industrial districts in Rio Grande do Sul, as well as oral sources and other materials that complemented the research. This dissertation is part of the Research Line "Migration and Labour", the Master course in History of Post -Graduate in History of the Federal University of Santa Maria that received funding from CAPES.